Addressing the C-Level Question: How Effectively are Assurance Functions Contributing and Using Automated Analytics?. Issue 5 (4th May 2017) - Cangemi, Michael P.
Abstract: This article addresses the questions: Are internal and external auditors on the correct path with their use of analytics? Is management getting what they need or are they shifting annual expense and capital investment away from audit and expanding their deployment of compliance functions to meet their responsibilities? We explore the expanding focus on the use of automated analytics by internal and external audit and summarize the recent Financial Executives Research Foundation research published in July 2016, titled: "Data Analytics and Financial Compliance: How Technology Is Changing Audit and Business Systems." We focus on internal audit and developments in the external audit, including a new project the American Institute of Certified Public Accountants and Rutgers University are leading called the Rutgers AICPA Data Analytics Research Initiative: looking into how the accounting firms can work together to advance their use of technology and analytics to improve audit effectiveness and efficiency.